A Prototype of Phase Lock Loop System on Communication Device for Motorcycle Riders - admin admin (PPM Telkom University, 2019)
In recent years, technology has developed rapidly, particularly technology in The telecommunication sector. As the electronic sector has been developing, as well as the increasing number of motorcycle riders and its communities, the authors are interested in designing an assistive device for motorcycle drivers. This device is designed as an additional communication tool for the coordination between the drivers. For communication, it is necessary to create a communication system without interfering with other riders. Therefore, the authors are motivated to design